Social theory since Freud : traversing social imaginaries - Elliott, Anthony, 1964- (Routledge, 2004)
This compelling book traces the rise of psychoanalysis from the Frankfurt School to postmodernism, exploring in detail the social and political factors that have led intellectuals to draw from the insights of Freud.